GENDER DALAM HUKUM ADAT - Sukerti, Ni Nyoman (Jurnal Studi Jender SRIKANDI, 2012)
The national government of Indonesia is committed to legal gender equality by the 1945 Indoensia Constitution, article 27 (1), and the ratification of the Convention for Elimination of all forms of Discrimination Against Women (CEDAW) in 1984. However, customary law still prevailing in many regions in Indoneia often perpetuates deeply rooted discrimination based on gender until today. Examples of such discrimination are to found in Minagkabau, Java, and Bali where inheritance is regulated by gender biased customary law. Appropriate development policies and education may bring about a legal culture and practice that upholds legal gender equality.
Keywords: GENDER